PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA KOMIK DIGITAL TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN CERITA FIKSI PADA SISWA DI SEKOLAH DASAR - Muhammad Alfigo; Sofyan Iskandar; Indah Nurmahanani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by digital comic media on the reading skills and comprehension of fiction stories in fourth gradeelementary scholl students in learning Indonesian. This research uses a quantitative approach with a quasi experimental design research type with a nonequivalent control group design. The sample used in this research was twenty five students in fourth grade C and fourth grade D. The results obtained from the influence of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by digital comic media on the reading skills and comprehension of fiction stories infourth grade elementary school students in learning Indonesian were 21%. So it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by digital comic media has an influence on the reading skills and comprehension of fiction stories in fourth grade elementary scholl students in learning Indonesian.